Gunshot-Related Injuries to the Foot & Ankle: Review Article. (April 2020) - Gonzalez, Tyler; Briceno, Jorge; Velasco, Brian; Kaiser, Philip; Stenquist, Derek; Miller, Christopher; Kwon, John Y.
Gunshot-related injuries remain a significant and important cause of global morbidity and cost. The foot and ankle has certain anatomic and functional considerations that make gunshot-related injuries challenging to manage. While the scientific literature regarding gunshot-related injuries is extensive, little of the existing literature focuses on the foot and ankle. While principles of management can be somewhat extrapolated from the current literature, an understanding of the body of work specific to the foot and ankle is valuable. Therefore, this review provides an overview of ballistic injuries to the foot and ankle as well as specific guidelines to aid surgeons in treating these difficult injuries. Level of Evidence: Level V, expert opinion.